Banking Risks around the World : The Implicit Safety Net Subsidy Approach - Laeven, Luc (World Bank, Washington, DC, 2014)
The author calculates gross safety net subsidies for a large sample of banks in 12 countries, to assess the relationship between the risk-taking behavior of banks, and certain ban characteristics. He finds that gross safety net subsidies are higher for banks that have concentrated ownership, that are affiliated with a business group, that are small, or that have high credit growth, and for banks in countries with low GDP per capita, high inflation, or poor quality, and enforcement of the legal system. These findings suggest that the moral hazard behavior of a bank depends on its institutional environment, and its corporate governance structure. The author also presents a matrix that shows estimates of safety net subsidies for a range of given combinations of equity volatilities, and equity-to-deposit ratios. These figures could be used as input to an early warning system, for both individual, and systemic banking problems.